Modelling ground thermal regime in bordering (dis)continuous permafrost environments - Hrbáček, Filip; Oliva, Marc; Fernández, Jesus-Ruiz; Kňažková, Michaela; de Pablo, Miguel Angel (Environmental research, 2020)
Permafrost controls geomorphological dynamics in maritime Antarctic ecosystems. Here, we analyze and model ground thermal regime in bordering conditions between continuous and discontinuous permafrost to better understand its relationship with the timing of glacial retreat. In February 2017, a transect including 10 sites for monitoring ground temperatures was installed in the eastern fringe of Byers Peninsula (Livingston Island, northern Antarctic Peninsula), together with one station recording air temperatures and snow thickness. The sites were selected following the Mid-Late Holocene deglaciation of the area at a distance ranging from 0.30 to 3.15 km from the current Rotch Dome glacier front. The transect provided data on the effects of topography, snow cover and the timing of ice-free exposure, on the ground thermal regime. From February 2017 to February 2019, the mean annual air temperature was -2.0 °C, which was >0.5 °C higher than 1986-2015 average in the Western Antarctic Peninsula region. Mean annual ground temperature at 10 cm depth varied between 0.3 and -1.1 °C, similar to the modelled Temperatures on the Top of the Permafrost (TTOP) that ranged from 0.06 ± 0.08 °C to -1.33 ± 0.07 °C. The positive average temperatures at the warmest site were related to the long-lasting presence of snow which favoured warmer ground temperatures and may trigger permafrost degradation. The role of other factors (topography, and timing of the deglaciation) explained intersite differences, but the overall effect was not as strong as snow cover.
Keywords: Snow cover; ostrovy; ekosystém; Maritime Antarctica; Permafrostdistribution; Ecosystem; Ground thermal regime; teoretické modely; Ice Cover; Permafrost; Islands; Models, Theoretical; permafrost; Antarktida; Antarctic Regions; Deglaciation; ledový příkrov